2011
DOI: 10.21608/ejabf.2011.2080
|View full text |Cite
|
Sign up to set email alerts
|

Rearing of the Nile tilapia (Oreochromis niloticus) on diets containing cotton seed meal enriched with vitamin E

Abstract: ABSTRACThe present experiment was conducted to evaluate the effect of α-tocopherol as an antioxidant for avoiding the side effects of incorporation of cottonseed meal (CSM) in the diet of the Nile tilapia as a replacer of fish meal (FM). Two diets were prepared; the first one contained fish meal and was considered as a control, in the second diet, FM was completely replaced by CSM. The second diet was divided into ten parts, the first one is a control and the other 9 diets were enriched with increased levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…The level of lipid peroxidation was significantly decreased in different tissues of DZNexposed fishes fed diets supplemented with vitamin E and/or lycopene. Similar results for vitamin E were observed in different fish (Abdel-Monem et al, 2012;Soltan et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The level of lipid peroxidation was significantly decreased in different tissues of DZNexposed fishes fed diets supplemented with vitamin E and/or lycopene. Similar results for vitamin E were observed in different fish (Abdel-Monem et al, 2012;Soltan et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Diet supplementation with LYC and/or VE for 14 and 28 days showed improvement in behavioral changes and the fishes were noticed in better conditions. Similar results for vitamin E and lycopene were observed by Ohaida (2005), Mekkawy et al (2011Mekkawy et al ( , 2013, Soltan et al (2011) andUral (2013). Diazinon insecticides induce oxidative stress leading to generation of free radicals and alteration in antioxidant enzymes or oxygen free radicals scavenging enzyme (ElShenawy et al, 2010).…”
Section: Discussionsupporting
confidence: 70%
“…Best FCR was also observed in treatment T4 indicating that good enrichment practice would positively affect the juvenile common carps. According to Solan et al (2011), incorporation of low concentration of vitamin E in to fish feed has positively improved the FCR in Tilapia. Parakrama et al (2011) have shown that vitamin E enriched feed has increased FCR in the post larvae of freshwater prawn.…”
Section: Discussionmentioning
confidence: 99%